2011
DOI: 10.1051/0004-6361/201016405
|View full text |Cite
|
Sign up to set email alerts
|

Propagating intensity disturbances in polar corona as seen from AIA/SDO

Abstract: Context. Polar corona is often explored to find the energy source for the acceleration of the fast solar wind. Earlier observations show omni-presence of quasi-periodic disturbances, traveling outward, which is believed to be caused by the ubiquitous presence of outward propagating waves. These waves, mostly of compressional type, might provide the additional momentum and heat required for the fast solar wind acceleration. It has been conjectured that these disturbances are not due to waves but high speed plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…We also measured the speeds of the PDs by producing time-slice images along the propagation direction (the solid lines in Figure 3). The speeds measured from these PDs vary from 70 to 170 km s −1 , which are consistent with previous results (Withbroe 1983;DeForest & Gurman 1998;Krishna Prasad et al 2011). In a few cases (see Figures 4(d), (f), and (g)), we found that the propagating structures have lower speeds (10-30 km s −1 ) near the limb before gaining much higher speed above it.…”
Section: Observations Data Analysis and Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…We also measured the speeds of the PDs by producing time-slice images along the propagation direction (the solid lines in Figure 3). The speeds measured from these PDs vary from 70 to 170 km s −1 , which are consistent with previous results (Withbroe 1983;DeForest & Gurman 1998;Krishna Prasad et al 2011). In a few cases (see Figures 4(d), (f), and (g)), we found that the propagating structures have lower speeds (10-30 km s −1 ) near the limb before gaining much higher speed above it.…”
Section: Observations Data Analysis and Resultssupporting
confidence: 80%
“…Although most of the PD structures are clearly seen below 1.1 R  (i.e., solar Y being 1050″), some PDs show clear structures reaching an altitude of 1.15 R  (i.e., solar Y being 1100″) or even higher. They are clearly present in power images at periodicities from 10 to 30 minutes, which are consistent with previous studies (DeForest & Gurman 1998;Banerjee et al 2000Banerjee et al , 2009Krishna Prasad et al 2011). To compare the PDs with spicules that were clearly visible in the AIA 304 Å channel, we further applied a simple bandpass filter to the AIA 171 Å images.…”
Section: Observations Data Analysis and Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…However, the interpretation of the observed perturbations has (again) come into question. Some authors still favour the propagating slow magneto-acoustic wave interpretation [41][42][43][44][45][46][47][48][49] but other authors have interpreted quasi-periodic disturbances with very similar properties as (quasi-periodic) upflows [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Several papers have reported on quasi-periodically occurring enhancements in the blue wing of the spectral line profiles that are co-located with the propagating disturbances, with motions of the same order of magnitude.…”
Section: Propagating Periodic Disturbancesmentioning
confidence: 99%
“…Techniques for measuring propagating intensity disturbances, which display translational motion parallel to the local magnetic field, have the greatest variety. Existing codes for detecting propagating disturbances utilize cross-and 2D coupled fitting methods (Yuan & Nakariakov 2012), the application of surfing transforms (Uritsky et al 2013), wavelets (Krishna Prasad et al 2011), and running difference images (Sheeley et al 2014). In contrast, methods for detecting transverse waves are less diverse.…”
Section: Introductionmentioning
confidence: 99%